Development of High-Strength Ring Bolt Manufacturing Technique Using Friction Welding - Chung, Hoyeon (International Journal of Engineering and Technology, 2019)
In this study, a ring bolt manufacturing technique using friction welding is proposed in order to improve the manufacturing process of the ring bolt. A ring bolt is an automotive part that fixes the position of the automobile’s handle when the handle is tilted. First of all, the shape design of the ring bolt is proposed and the optimum friction welding conditions, which directly affect the quality of friction welding, are derived. The experimental results show that the tensile strength (load) of the ring bolt, manufactured using friction welding, is better by 12% than that of products manufactured via the conventional method.
Keywords: Ring bolt; Friction welding; Optimum friction welding factor; Welding condition